Comparison of Pain Scores During Retrieval of Ureteral Stents Using Rigid Cystoscope Versus Rigid Ureteroscope in an Office Setting: A Prospective Study - Siddalingeshwar I Neeli; Sree Harsha Nutalpati (Journal of Urological Surgery, 2020)

(untitled)
Objective:Ureteral stents inserted to prevent obstruction to the flow of urine need to be removed after they serve the purpose of their insertion. The most commonly practiced method for stent removal is using a rigid cystoscope in an office setting. However, it is quite painful and may require general anesthesia especially in males. Due to their small caliber, rigid ureteroscope can reduce patient discomfort during ureteral stent retrieval procedure. In this study, we compared the pain scores during ureteral stent retrieval using a rigid cystoscope and a rigid ureteroscope.Materials and Methods:A prospective study was conducted with 64 male patients with ureteral stents who were divided into two groups. Group A had 36 patients who underwent stent retrieval with rigid cystoscope while group B had 28 patients who underwent with rigid ureteroscope. Pain experienced during the procedure and during the first void thereafter were recorded using visual analog scale.Results:The patients who underwent stent retrieval using rigid cystoscope (mean 7.05±1.21) had a significantly higher (p<0.0001) pain score compared to those who underwent it using rigid ureteroscope (mean 2.57±1.04). The pain scores during the first void after the procedure as reported by patients in groups A and B were 6.58±1.27 and 3.03±0.96 (p<0.0001), respectively.Conclusion:Rigid ureteroscopic stent retrieval is a less painful, safe, and dependable method, with a reduced requirement for postoperative analgesics as compared to rigid cystoscopic stent retrieval.